Ultra-trace measurement of Dechloranes to investigate food as a route of human exposure. (November 2015) - L'Homme, Benjamin; Calaprice, Chiara; Calvano, Cosima Damiana; Zambonin, Carlo; Leardi, Riccardo; Focant, Jean-François
Highlights: This is the first report on levels of Dechloranes in European Food and feed. A specific GC-QQQMS/MS method was developed. Most selected Dechloranes were detected in European food and feed. Dechloranes are at the pg/g fat levels in food. A Dechlorane dietary intake was estimated for the Belgian population. Abstract: Dechloranes, including Dechlorane Plus (syn- and anti-isomers), Dechlorane 602, Dechlorane 603, Dechlorane 604, Chlordene Plus, and Mirex are used as flame-retardants and were recently found in human serum of the European population. In order to investigate if food consumption would possibly be a significant route of exposure, we developed a method for the measurement of Dechloranes in food and feed. We showed that it was possible to extend the scope of the regular polychlorinated dibenzo- p -dioxins (PCDDs), polychlorinated dibenzofurans (PCDFs), dioxin like (DL-), and non-dioxin like (NDL-) regulated PCBs clean-up and fractionation procedure to Dechloranes and that no compound degradation occurred during the strong acidic treatments used for lipid digestion. Dechloranes were measured by gas chromatography coupled to triple quadrupole mass spectrometry (GC-QQQMS/MS). We optimized injection parameters by face centered experimental design (FCD). The electron ionization fragmentation was investigated to set appropriate multiple reaction monitoring (MRM) transitions. Instrumental and method limits of quantitation (iLOQs and mLOQs) were determined following EU guidelines for dioxin analyses in food. A total of 88 samples were analyzed to assess the prevalence of this route of exposure to humans. Average levels of the sum of Dechloranes ranged from 10 to 31 pg/g fat, with the exception of fish, feed additives, and corn that were reported in pg/g wet weight at average levels of 9, 12, and 2 pg/g ww. Based on Belgian food habits, a dietary intake was estimated to be 136 pg/day. The relatively low reported levels indicate that other routes of human exposure should be considered.